A bell pull hung from the ceiling of the reception hall - Mumbai Archive Project (Jio Institute, 2024)
The Club of St. Anthony has trappings of a space from another era, caught in a time-wrap. A curious anachronistic detail is a bell pull hung from the ceiling of the reception hall. The bell is connected to a wire that can be pulled from outside to alert the manager if a visitor finds the gate locked from inside. There is no electric calling bell.